'Everything is different’: the impact of acquiring aphasia on information seeking - Birgit Kvikne; Gerd Berget (Information Research: An International Electronic Journal)
Introduction. Aphasia is a language impairment that can lead to significant changes in all aspects of life, including information-seeking behaviour. This paper presents findings from a qualitative study exploring how acquiring aphasia impacts information seeking. The study also assesses the applicability of the information behaviour theory of transitions as a framework to explore and understand this life change in the context of information-seeking behaviour.